The Role of School Counsellor to Handling Student Sexual Harassment Behavior in the School - I Putu Agus Apriliana (Universitas Negeri Padang, 2018)
Sexual harassment behavior by students is an international phenomenon. So that, this article presents and describes the role of school counsellor in handling the phenomenon of student’s sexual harassment behavior in the school environment. This article is expected to provide knowledge and insight to school counsellor to help student’s (client) achieve optimum overall development, especially the result of sexual harassment acts. Sexual harassment behavior can cause (victims) to experience physical and psychological disorders. This pattern of behavior is in the form of verbal, non-verbal and physical. The school counsellor strategy for dealing with this behavior namely collecting information, providing treatment in the form of counseling sevices for victims and choaching for the perpetrators, and conducting evaluation and follow-up. Furthermore, school counsellor strategy to prevent this behavior namely through basic services and create a good relationship with students. Through this article, it is hoped that the understanding of school counsellor on the student’s sexual harassment behavior and the handling efforts can be increased, so it will be able to provide maximum service to the students to achieve optimum development.